THE MAN 1 NGANJUK WEBSITE REDESIGN - Hartono, Ahmad Fuji (Arty: Jurnal Seni Rupa, 2019)
MAN 1 Nganjuk is one of the educational institutions with islamic education background who are in the area Kab. Nganjuk, which is located at Jl. KH. Abdul Fattah, Ds. Nglawak, Kec. Kertosono, Kab. Nganjuk, East Java. At this time, information needs are increasingly high which includes academics and non-academics. This encourages MA Negeri 1 Nganjuk to redesign the online information media (website) that is easily accessible, easy to understand, and can be utilized as a means of registering new student. The design of the study project was designed through 4 stages, namely is preliminary process, pra-production process, production process, and pasca-production process. The design of all these works pays attention to design elements such as line, fields, spaces, and colors. Design principles such as balance, domination and unity are also used so as to create an aesthetic design. The types of massages contained in information media are informative, interactive, remiders, adding value and helping other activities. The redesign of the website’s work and its application to the information, more actual, and be able to be a source of information that can be used as a resource for internet users about the instituion. It also provides good image and service as an educational institution in front of the wider community in accordance with the vision and mission of the school, and the media that has been designed can also be distributed according to the intended target audience